Children and adolescents with type 1 and type 2 diabetes mellitus in the Pediatric Diabetes Consortium Registries: comparing clinical characteristics and glycaemic control. Issue 5 (5th February 2020) - Van Name, M. A.; Cheng, P.; Gal, R. L.; Kollman, C.; Lynch, J.; Nelson, B.; Tamborlane, W. V.; ,
Abstract: Aim: To compare the characteristics of children and adolescents with type 1 vs. type 2 diabetes in the Pediatric Diabetes Consortium (PDC) registries. Methods: Participants were 10 to < 21 years of age at diagnosis; there were 484 with type 1 diabetes and 1236 with type 2 diabetes. Results: Children and adolescents with type 2 diabetes were more likely to be female, overweight/obese, and from low‐income, minority ethnic families. Children and adolescents with type 1 diabetes were more likely to present with diabetic ketoacidosis and have higher mean HbA1c levels at diagnosis. More than 70% in both cohorts achieved target HbA1c levels < 58 mmol/mol (< 7.5%) within 6 months, but fewer participants with type 1 than type 2 diabetes were able to maintain target HbA1c levels after 6 months consistently throughout 3 years post diagnosis. Of the 401 participants with type 2 diabetes with ≥ 24 months diabetes duration on enrolment in the registry, 47% required no insulin treatment. Median C‐peptide levels were 1.43 mmol/l in the subset of participants with type 2 diabetes in whom it was measured, but only 0.06 mmol/l in the subset with type 1 diabetes. Conclusions: Although families of children and adolescents with type 2 diabetes face greater socio‐economic obstacles and risk factors for poor diabetes outcomes, the greater retention of residual endogenous insulin secretion likely contributes to the increased ability of children and adolescents with type 2 diabetes to maintain target HbA1c during the first 3 years of diabetes diagnosis. What's new?: Demographic and anthropometric characteristics differ between children and adolescents with type 1 and type 2 diabetes in the Pediatric Diabetes Consortium Registries. Although a large percentage of older children and adolescents with type 1 and type 2 diabetes are able to achieve target HbA1c levels after 6 months of treatment, children and adolescents with type 2 diabetes are more likely to maintain glycaemic control than those with type 1 diabetes in the years after diagnosis, despite greater socio‐economic obstacles and risk factors. More intensive treatment strategies are needed to maintain target HbA1c levels in older children and adolescents with type 1 diabetes after the initial 6‐month honeymoon period.